Comfort properties of bamboo cotton 1X1 rib knitted fabrics / Nadhirah Mohd Amran - Mohd Amran, Nadhirah (2018)
Moisture management, water vapour permeability, air permeability, and thermal conductivity properties are important factors that could decide the comfort level of clothing worn by humans. In this study, these comfort properties were investigated on thirteen lxl rib knitted fabrics produced using scoured 100% cotton yarn (30 Tex) and 100% bamboo yarn (37 Tex) with different arrangement of cotton and bamboo yarn. The results showed that the treated fabrics have better overall moisture management properties, water vapour permeability, and thermal conductivity while the untreated fabrics have better air permeability. The increase of bamboo yarn in the combination of bamboo/cotton fabrics decreased the moisture management properties but improved the thermal conductivity of the fabrics. It was found that the position and arrangement of the bamboo and cotton yarns in the fabrics affect the fabric's moisture management and thermal conductivity. Statistical analysis using SPSS showed that the moisture management was not influenced by loop length while the water vapour permeability was not influenced by the courses/cm of the cotton fabrics. However, all the physical properties did influence the air permeability including course/cm, wales/cm, weight, thickness, and loop length. In addition, the weight and loop length of bamboo did not influence the thermal conductivity.